Method of determining the efficiency of heliocollector in system with forced circulation of coolant - Voznyak, O.; Pona, O.; Shapoval, S.; Spodyniuk, N.; Eltman, A. (КНУБА, 2015)
The potential of solar energy for Poland is analyzed. The efficiency of solar collectors installed in the mechanical heating system is researched.The dependences between the angles fall heat flux and intensity of the heat flux on the effectiveness of solar collector is established.
Методика визначення ефективності геліоколектора у системі з вимушеною циркуляцією теплоносія
Методика определения эффективности геллиоколектора в системе с принудительной циркуляцией теплоносителя
Keywords: solar energy; mechanical heating system; the angles fall heat flux; the heat flux; 620.97:697.329